The Lady's Magazine (1770-1832) and the Making of Literary History - Batchelor, Jennie (Edinburgh University Press, 2023)
The first major study of one of the most influential periodicals of the eighteenth and nineteenth centuriesProvides the first major study of one of the most influential periodicals of the eighteenth and nineteenth centuriesInterrogates and revises critical commonplaces and narratives about form, authorship, reading and gender through rigorous archival research on the magazine's authors, readers, printers and publishersMaps new directions in eighteenth-century and Romantic studies, women's writing, and media and cultural history by modelling innovative and interdisciplinary methodologies for historical periodical studiesMoves the women's magazine from the periphery to the centre of eighteenth-century and Romantic print cultureIn December 1840, Charlotte Brontë wrote in a letter to Hartley Coleridge that she wished 'with all [her] heart' that she 'had been born in time to contribute to the Lady's magazine'. Nearly two centuries later, the cultural and literary importance of a monthly publication that for six decades championed women's reading and women's writing has yet to be documented. This book offers the first sustained account of The Lady's Magazine. Across six chapters devoted to the publication's eclectic and evolving contents, as well as its readers and contributors, The Lady's Magazine (1770-1832) and the Making of Literary History illuminates the periodical's achievements and influence, and reveals what this vital period of literary history looks like when we see it anew through the lens of one of its most long-lived and popular publications.